Deep eutectic solvent assisted electrosynthesis of ruthenium nanoparticles on stainless steel mesh for electrocatalytic hydrogen evolution reaction. (1st August 2021) - Edison, Thomas Nesakumar Jebakumar Immanuel; Atchudan, Raji; Karthik, Namachivayam; Chandrasekaran, Sundaram; Perumal, Suguna; Raja, Pandian Bothi; Perumal, Veeradasan; Lee, Yong Rok
Graphical abstract: Highlights: Cost effective electro-synthesis of RuNPs on stainless steel has been developed. Deep eutectic solvent was used for the electrodeposition process. The electro-synthesized RuNPs act as good HER electrocatalyst in H2 SO4 . Abstract: Deep eutectic solvents (DES) are considered as a green non-toxic electrolyte for the replacement of cyanide based toxic electrolytes towards the electrodeposition of noble metal and alloy nanoparticles on conducting surfaces. In this work, ruthenium nanoparticles (RuNPs) are electrochemically synthesized over cathodically treated stainless-steel mesh (CSS) by applying the cathodic current of −15 mA/cm 2 using ruthenium chloride and deep eutectic mixture consists of choline chloride/urea as electrolyte. The resulting material is abbreviated as RuNPs@CSS and are characterized by surface analytical tools such as X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning elctron microscopy with energy dispersive spectrum (FE-SEM with EDS). Further, the electrocatalytic hydrogen evolution reaction (HER) activity of RuNPs@CSS is accessed and compared with state of art Pt electrode using open circuit potential (OCP), linear sweep voltammetry (LSV), Tafel plot and electrochemical impedance spectroscopy (EIS) measurements in 0.5 M H2 SO4 . The calculated HER's onset potential and over potential @ −10 mA/cm 2 of RuNPs@CSS are about −0.0273 and −0.0657 V vs. RHE, which are very close to the bare Pt values. The EIS results suggested that, RuNPs@CSS possess excellent conductivity, which decrease the charge transfer resistance and enhances the HER. This study proved that the electrodeposited RuNPs@SS is better replacement for Pt based electrocatalysts towards acidic HER.